1981
DOI: 10.1111/j.1476-5381.1981.tb09961.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms of Action of Histamine in Isolated Arteries of the Dog

Abstract: 1 In helically-cut strips of dog coronary, superior mesenteric, right gastro-epiploic and renal arteries contracted with prostaglandin F2X (PGF21), histamine produced a dose-related relaxation, while, in contrast, the amine caused only a contraction of cerebral arterial strips. 2 The contractile response of cerebral arteries to histamine was attenuated by chlorpheniramine (10-6M) but was unaffected by cimetidine (10-5M). Relaxant responses to histamine of coronary and renal arteries were significantly attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…These results suggest that histamine-induced increases in coronary blood flow are mediated by activation of both histamine Hl-and H2-receptors. Recently, Konishi et al, (1981), using the helical strips of dog coronary artery, reported that the relaxant response to histamine was mediated by histamine H2-receptors since it was attenuated by cimetidine but was not influenced by chlorpheniramine. It is obvious that such isolated preparations consist of relatively large size vessels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that histamine-induced increases in coronary blood flow are mediated by activation of both histamine Hl-and H2-receptors. Recently, Konishi et al, (1981), using the helical strips of dog coronary artery, reported that the relaxant response to histamine was mediated by histamine H2-receptors since it was attenuated by cimetidine but was not influenced by chlorpheniramine. It is obvious that such isolated preparations consist of relatively large size vessels.…”
Section: Resultsmentioning
confidence: 99%
“…In the dog coronary circulation, however, there is little information concerning the role of histamine Hl-and H2-receptors in mediation of the vascular effects of histamine. Recently, Konishi, Toda & Yamamoto (1981) showed that relaxation of helically-cut strips of the dog coronary artery induced by histamine was mediated by histamine H2-receptors. The present study provides evidence for HI-receptor mediated prejunctional inhibition of cardiac sympathetic nerve function and for both H1-and H2-receptor mediated coronary vasodilatation.…”
Section: Introductionmentioning
confidence: 99%
“…Ang II in a concentration of 10-7 M or histamine in a concentration of 10-6 M was added, and after the tension had returned and stabilized, PGI2 (10-8M) and isoprenaline (10-7M) were added. The concentration of Ang II used was sufficient to produce the maximum relaxation (Toda & Miyazaki, 1981), and the concentration of histamine was approximately the median effective concentration (Konishi et al, 1981). At the end of each series of experiments, papaverine (10-4M) was added to produce the maximum relaxation (Toda, 1974); relaxations induced by Ang II, histamine, PGI2, isoprenaline or acetylcholine relative to those induced by papaverine are presented.…”
Section: Methodsmentioning
confidence: 99%
“…In response to histamine, dog mesenteric, gastroepiploic, and renal arteries relax, 1 but dog cerebral arteries of the proximal portion, pulmonary and mesenteric arteries, and pulmonary and portal veins constrict.…”
mentioning
confidence: 99%